CITRA PEREMPUAN DALAM LIRIK LAGU KIMCIL KEPOLEN KARYA NDX AKA FAMILIA DALAM PERSPEKTIF LINGUISTIK KOGNITIF - Ferdi Arifin (Jurnal Bahasa Lingua Scientia, 2017)
Kimcil Kepolen song is a dangdut hiphop and being popular song nowadays. This song is created by NDX a.k.a Familia that inspires people for his long journey as a labor towards a great Indonesian musician that has been loved by widely society. This lyric represents women image from NDX perspective before his successful being a great musician. The study employs qualitative method to look at Kimcil Kepolen lyric as a language fact which is able to be examined by semantic and cognitive linguistics perspective. The results shows us that Kimcil Kepolen lyric represents materialistic women are being hard to get engage and to make a serious relationship for poor men. The facts explain that materialistic women are easily breaking men’s heart and cheating to a man who has a stabble financial support.